Effects of physical activity on depression, anxiety, and stress in college students: the chain-based mediating role of psychological resilience and coping styles - Liu, Ming; Liu, Huanju; Qin, Zhuzhu; Tao, Yining; Ye, Wan; Liu, Renyang (Frontiers in Psychology, 2024)
Background Physical activity can alleviate negative emotions in college students by enhancing mood and cognitive functions. Yet, the mechanisms underlying these benefits remain unclear. Purpose This study examines the association between physical activity and negative emotions—specifically, depression, anxiety, and stress—in college students. Additionally, we explore the mediating effects of psychological resilience and coping styles to offer theoretical and practical insights for mitigating students’ negative emotions. Methods Using a stratified random sampling approach, a total of 1,380 college students, from five universities in Hangzhou, Nanjing, and Wenzhou, were included in the analysis. The survey instruments included the Physical Activity Rating Scale, Connor-Davidson Resilience Scale, Simple Coping Style Scale, and Depression-Anxiety Stress Scale. The data were statistically analyzed using multivariate methods with IBM SPSS 25.0 and the PROCESS V3.3 plug-in. Results (1) College students engage in a low level of physical activity, with male students participating significantly more than female students (p < 0.001). (2) Physical activity was significantly positively correlated with psychological resilience and positive coping styles (t = 9.126, p < 0.001; t = 23.087, p < 0.001) and overall negative correlated with negative emotions in college students (t = −3.601, p < 0.001). (3) Psychological resilience and positive coping styles were found to play a chain mediating role between physical activity and negative emotions. The mediation effect consists of two paths: physical activity → psychological resilience → negative emotions (effect value: −0.0324), and physical activity → psychological resilience → positive coping → negative emotions (effect value: −0.0099). (4) Female students demonstrated higher levels of positive coping (p < 0.001), while male students exhibited more negative emotions (p < 0.001). Conclusion Our study identifies a significant indirect link, mediated by psychological resilience and positive coping styles, between physical activity and the reduction of negative emotions. Targeted interventions addressing gender differences, such as offering special courses and providing specialized exercise programs and emotional management strategies, can enhance psychological resilience and positive coping mechanisms. Consequently, these measures can alleviate the adverse effects of negative emotions. Our findings have broader implications for both research and practical interventions in promoting mental health among college students.